Yarning up about out‐of‐pocket healthcare expenditure in burns with Aboriginal families - Courtney Ryder; Tamara Mackean; Kate Hunter; Julieann Coombes; Andrew J.A. Holland; Rebecca Ivers (Elsevier, 2021)
Abstract Objective: This study sought to understand the impact of out‐of‐pocket healthcare expenditure (OOPHE) on Aboriginal families of children with acute burns injury. Methods: Families participating in a larger Australia‐wide study on burns injuries in Aboriginal and Torres Strait Islander children were approached to participate. Decolonising methodology and yarning were employed with participants to scope OOPHE for burns care. Thematic analyses were used with transcripts and data organised using qualitative analysis software (NVivo, Version 12). Results: Six families agreed to participate. Four yarning sessions were undertaken across South Australia, New South Wales and Queensland. The range of OOPHE identified included: costs (transport, pain medication, bandages), loss (employment capacity, social and community) and support (family, service support). The need to cover OOPHE significantly impacted on participants, from restricting social interactions to paying household bills. Close family connections and networks were protective in alleviating financial burden. Conclusion: OOPHE for burns care financially impacted Aboriginal families. Economic hardship was reported in families residing rurally or with reduced employment capacity. Family and network connections were mitigating factors for financial burden. Implications for public health: Targeted support strategies are required to address OOPHE in burns‐related injuries for Aboriginal communities.